Psychophysical acting: an intercultural approach after Stanislavski, by Phillip B. Zarrilli - Cordeiro, Marcelo (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2026)
This review focuses on the second part of Phillip B. Zarrilli’s book Work on oneself (2009), with a preface by Eugenio Barba. Centered on the psychophysical dimension of acting, the selected section addresses the importance of the actor’s psychic dimension and the ability to work on oneself.